Effect of Calcination Temperature on the Synthesis of ZrO2-Pillared Saponite to Catalytic Activity in Menthol Esterification - Is Fatimah; Dwiarso Rubiyanto; Nanda Candra Kartika (Universitas Gadjah Mada, 2016)
The influence of calcination temperature on the synthesis of zirconia-pillared saponite (PILS) and on its catalytic activity in menthol esterification has been studied. Zirconia pillarization was conducted using zirconium tetraisopropoxide as a precursor and with calcination temperatures of 450, 600 and 700 °C. Evaluation of physicochemical characteristics at these varied temperatures was carried out by X-Ray Diffraction (XRD), surface area analysis, Scanning Electron Eicroscope (SEM) analysis, Differential Thermal Analysis (DTA) and total acidity. The obtained results indicate that the structure and surface acidity of saponite were strongly influenced by calcination temperature. The solid acidity and surface parameters such as specific surface area, pore volume, and pore radius play an important role in the total conversion and selectivity in menthol esterification.